Population-based study of mortality and major amputation following lower limb revascularization. Issue 9 (25th April 2018) - Heikkila, K; Loftus, I M; Mitchell, D C; Johal, A S; Waton, S; Cromwell, D A
Abstract: Background: The aim of this study was to estimate separate risks of major lower limb amputation and death following revascularization for peripheral artery disease (PAD) using competing risks analysis. Methods: Routinely collected data from Hospital Episode Statistics (HES) were used to identify patients who underwent endovascular or open lower limb revascularization for PAD in England from 2005 to 2015. The primary outcomes were major lower limb amputation and death within 5 years of revascularization. Cox proportional hazards and Fine–Gray competing risks regression were used to examine the competing risks of these outcomes. Results: Some 164 845 patients underwent their first lower limb revascularization for PAD during the study interval. Most were men (64·6 per cent) and the median age was 71 (i.q.r. 62–78) years. Following endovascular revascularization, the 5-year cumulative incidence of amputation was 4·2 per cent in patients with intermittent claudication and 18·0 per cent in those with a record of tissue loss. The corresponding rates were 10·8 and 25·3 per cent respectively after open revascularization, and 8·1 and 25·0 per cent after combined procedures. The 5-year cumulative incidence of death varied from 24·5 to 39·8 per cent, depending on procedure type. Competing risks methods consistently produced lower estimates than standard methods. Conclusion: The 5-year risk of major amputation following lower limb revascularization for PAD appears lower than estimated previously. Patients undergoing revascularization for tissue loss and those who require an open procedure are at highest risk of limb loss. Abstract : Lower than previously estimated